2020
DOI: 10.1007/s13760-020-01401-7
|View full text |Cite
|
Sign up to set email alerts
|

A complication of coronavirus disease 2019: delirium

Abstract: COVID-19 is predominantly a respiratory disease. However, some cases exhibit other features including Central Nervous System symptoms. In the older adult, COVID-19 may present with atypical symptoms, including delirium and its complications. The objective of this study is to describe the relationship between the new type of coronavirus infection and delirium. Systematic research (Cochrane Library and PubMed) was carried out (only upper time limit: April 2020). Publications found through this indexed search wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 28 publications
1
40
0
9
Order By: Relevance
“…Other authors acknowledge delirium as a complication of COVID-19 and state that the presence of comorbidities found during the SARS-CoV-2 infection may facilitate the onset of an acute confusional state [ 47 ]. Independent of the etiology of delirium, hospitals should consider adding mental status changes to the list of testing criteria since delirium may be the only presenting symptom [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other authors acknowledge delirium as a complication of COVID-19 and state that the presence of comorbidities found during the SARS-CoV-2 infection may facilitate the onset of an acute confusional state [ 47 ]. Independent of the etiology of delirium, hospitals should consider adding mental status changes to the list of testing criteria since delirium may be the only presenting symptom [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nurses involved in our study mentioned that family involvement was limited to practicalities and they missed the presence of the family, especially in situations the patient was delirious or anxious. It is suggested that the incidence of delirium among COVID-19 hospitalized patients is rising, probably due to the isolation measures and personal protective equipment of the healthcare professionals ( Mcloughlin et al., 2020 , Cipriani et al., 2020 ). Because family can play an important role in the prevention and treatment of delirium ( McKenzie and Joy, 2020 ), research on how to involve family in the care for delirious patients during periods of visiting restrictions is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…The biologically-mediated effects of COVID-19 infection have been shown to be multifaceted. Among the many clinical manifestations a variety of neuropsychiatric symptoms (1) and delirium (2) have been observed in patients with severe COVID-19 infection, even in the absence of any other symptoms/signs. Likewise, the psycho-social impact of this pandemic on the mental health of the general population, as well as of frontline workers and people with pre-existing psychiatric conditions, has been extensively documented (3).…”
Section: Introductionmentioning
confidence: 99%